Deskripsi Kemandirian Anak Ditinjau dari Pola Asuh Orang Tua di TK Dewi Sartika Kecamatan Sipatana Kota Gorontalo - Winrista Minahali; Icam Sutisna; Sri Rawanti (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Abstract. Winrista Minahali, 2024. Description of Children's Independence Reviewed from Parenting Patterns at Dewi Sartika Kindergarten, Sipatana District, Gorontalo City, Faculty of Education, Gorontalo State University. Supervisor 1: Icam Sutisna, S.Pd., M.Pd and Supervisor II: Sri Rawanti, S.Pd., M.Pd. The formulation of the problem in this study is "How is the Description of Children's Independence Reviewed from Parenting Patterns at Dewi Sartika Kindergarten, Sipatana District, Gorontalo City". This study aims to determine how the description of children's independence is reviewed from parenting patterns at Dewi Sartika Kindergarten, Sipatana District, Gorontalo City. This study uses a qualitative descriptive method. Data collection was carried out by observation, documentation and interviews. The data analysis techniques used were data reduction, data display and verification. Based on the results of the research and the discussion described, it can be concluded that democratic parenting supports children's independence, characterized by the child's ability to take the initiative, be confident, not depend on others, and be able to solve problems independently. In contrast, permissive and authoritarian parenting tend to inhibit these aspects. This study emphasizes the importance of the role of parents in providing the right space for children to learn independently according to their developmental stage.